Experimental Investigation on Flame Chemiluminescence and Flow Characteristics of a Reverse-Flow Combustor - Ge Hu; Jianzhong Li; Wu Jin; Jingzhou Zhang; Li Yuan (International Journal of Aerospace Engineering)
The reverse-flow combustor is extensively applied in small engines due to its compact structure. The cold-state flow characteristics, the ignition process, and flame chemiluminescence characteristics of the reserve-flow combustor were investigated experimentally. Using the particle imaging velocimeter, the cold-state time-averaged flow fields at three different total pressure loss coefficients ζB are examined. The ignition processes of the combustor, as well as flame characteristics during stable combustion at different equivalent ratios φ, are analyzed based on flame chemiluminescence imaging when ζB is 3%. As ζB increases from 1% to 5%, the flow field of the combustor remains almost unchanged while the flow velocity increases. For ζB =3%, the ignition time T drops from 26 ms to 16 ms with an increase of φ. In addition, the ignition performance is enhanced. Proportions of the T2 phase (quasi-stable phase) are 73%, 68%, and 66%, respectively, suggesting that the quasi-stable phase is the key to successful ignition. As φ increases, the flame becomes thinner and shorter. Furthermore, standard deviations of continuous image areas of CH∗ and OH∗ drop from 0.0143 and 0.0132 to 0.0115 and 0.0109, respectively, which indicates the enhancement of combustion stability. According to the brightness distributions of CH∗ and OH∗ along the axial direction of the combustor at different equivalent ratios, the production of OH∗ is significantly affected by the temperature. It can be adopted as an important sign of heat release during combustion.